The Environmental Evaluation of the Sp. Opi – Babatan Saudagar – Srijabo Road: Evaluasi Lingkungan Ruas Jalan Sp. Opi – Babatan Saudagar – Jalan Srijabo - Armo, Achmad Abraham Setiawan; Wijaya, Hendry; Sutejo, Yulindasari; Saloma; Juniah, Restu; Fathunnisa (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
The Public Works Agency for Highways and Spatial Planning of South Sumatra Province has the task of deconcentration in the field of roads and has authority over 88 roads with a length of 1,779.27 km spread across 17 districts and cities in South Sumatra Province. Not all provincial roads have an environmental evaluation document. The objective of the current research was to evaluate the environmental impact resulting from road operational activities in South Sumatra Province by taking data on ongoing activities, geological and topographic conditions, flora and fauna, socio-economic and cultural activities in the area, as well as measuring quality standards, which include air quality standards, noise, vibration, and water quality standards on the Sp. OPI - Babatan Saudagar - Srijabo Road. The conclusion of the current research shows that the ambient air quality, noise intensity, and vibration are still good and meet quality standards. The potential hydrogen (pH) and dissolved oxygen (DO) parameters in the Ogan River branch at the time of sampling for surface water quality did not meet the quality standards due to the type of soil, which tends to be acidic. Furthermore, the results of groundwater quality analysis show that the pH of groundwater measured in all locations is less than 6.5 or does not meet quality standards, which can cause an unpleasant taste when consumed, so processing is needed to increase the pH of groundwater.